2020
DOI: 10.1101/2020.10.22.20217620
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying Geographic Heterogeneity in TB Incidence and the Potential Impact of Geographically Targeted Interventions in South and North City Corporations of Dhaka, Bangladesh: A model-based Study

Abstract: Background: In rapidly growing, high burden urban centers, identifying tuberculosis (TB) transmission hotspots and understanding potential impact of interventions can inform future control and prevention strategies. Methods: Using data on local demography, TB reports, and patient reporting patterns in Dhaka South City Corporation (DSCC) and Dhaka North City Corporation (DNCC), Bangladesh, between 2010 and 2017, we developed maps of TB reporting rates across wards in DSCC and DNCC and identified wards with high… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The estimates were then adjusted for observed correlations between TB notifications and actual residence to reflect that 50% of the randomly selected TB cases reported that they resided outside of the ward of their TB diagnosis and treatment. [2] Demographic health survey in Bangladesh Sociodemographic factors including age, sex, education level and wealth index, were extracted from the BDHS conducted in 2013-2014, which was the most recent publicly available data at the time of analysis. The BDHS uses a two-stage stratified sampling design that divides the population of Bangladesh into 600 enumeration areas (EAs, 'clusters').…”
Section: National Tb Notification Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The estimates were then adjusted for observed correlations between TB notifications and actual residence to reflect that 50% of the randomly selected TB cases reported that they resided outside of the ward of their TB diagnosis and treatment. [2] Demographic health survey in Bangladesh Sociodemographic factors including age, sex, education level and wealth index, were extracted from the BDHS conducted in 2013-2014, which was the most recent publicly available data at the time of analysis. The BDHS uses a two-stage stratified sampling design that divides the population of Bangladesh into 600 enumeration areas (EAs, 'clusters').…”
Section: National Tb Notification Datamentioning
confidence: 99%
“…each EA should consist of a certain number of wards), this process was imprecise given the rapid changes and urbanisation occurring in Dhaka during this time period. The BDHS sampled 20-30 households per EA, covering all the seven divisions and 64 districts of Bangladesh, based on the 2011 Population and Housing Censusbut did not include wards in the sampling frame per se [2]. DCC contains 23 EA-level clusters, including surveys of 610 households and 2641 individuals.…”
Section: National Tb Notification Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, spatial clusters of closely related Mtb strains may indicate local areas of ongoing transmission, which could be targeted for public health interventions such as active case finding (3)(4)(5)10). A growing body of evidence suggests that geographically targeted interventions may be effective and cost-efficient in high-burden, low-resource settings, and could be instrumental in accelerating progress toward TB elimination (4,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%